Optimalisasi Pemanfaatan Limbah Peternakan Sapi Perah sebagai Upaya Peningkatan Kualitas Lahan Pertanian Berbasis Pertanian Urban - Qomariah, Umi Kulsum Nur; Hidayat, Rohmat; Susanti, Ambar; Ahmidah, Silfi Alfi; Fatiha, Ulan Supartini; Wijayanti, Sri; Ahmad, Dziqi Jamaludin (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
In the context of urban agriculture, the utilization of livestock waste is key to improving the quality of agricultural land. Liquid organic fertilizer is one of the products derived from dairy farm waste and other organic materials. This article discusses a community service program run in Murukan Village, which is the center of dairy farming and has great potential in farm waste management. Although cow's milk is the identity of this village, farm waste that has the potential to be used to improve agriculture is still underutilized. In order to optimize the use of livestock waste, the community service team designed and conducted training with the theme